Does rural land consolidation improve the environmental efficiency of grain production? A quasi-natural experiment based on China’s high-standard farmland construction policy - Sun, Shufang; Zhang, Ruilin (Frontiers in Sustainable Food Systems, 2025)
IntroductionWith the global population growing and arable land becoming increasingly scarce, ensuring food security and promoting sustainable agricultural practices have become critical global priorities. This study investigates the environmental efficiency of grain production in China, focusing on the impact of the high-standard farmland construction (HSFC) policy.MethodsUsing panel data from 30 Chinese provinces from 2007 to 2022, the study employs a superefficient slack-based measure (SBM) model to assess the environmental efficiency of grain production, considering both desired and undesired outputs. A continuous difference-in-differences (DID) model is applied to examine the effects and mechanisms of the HSFC policy.ResultsThe study finds that: (1) the overall environmental efficiency of grain production in China is improving, although the rate of improvement diminishes from the eastern to the central and western regions; (2) the HSFC policy positively influences environmental efficiency, especially in the eastern region and areas with significant land transfers; and (3) the policy enhances efficiency primarily through the promotion of larger-scale farming operations and improved agricultural services.DiscussionThe findings suggest that the HSFC policy plays a key role in improving the environmental efficiency of grain production, particularly in regions with more advanced agricultural infrastructure. These results emphasize the importance of tailoring agricultural policies to regional conditions. It is recommended that both Chinese and other developing nations customize their agricultural strategies to ensure grain security and foster sustainable agricultural development.